A formação de professores para o ensino profissional e tecnológico mediado pela metodologia por competências a partir dos anos 70 - Andrade, Maria do Carmo Ferreira de (2015)
This dissertation studies Teachers Training on Professional and Technological Education mediated by the Abilities Methodology in Brazil, starting in the 70’s. We will research Teachers Training on this area with its regulations and benchmarks in Brazil’s legislation, analyzing relevant bibliography to its implementation. In order to find traces of the theme we covered its history and the starting point of Professional Education which was the creation of the “Escola de Aprendizes Artíficies” by the Federal Government that established free professional education in all the capitals of the Brazilian states. The organic laws that created the “S” system with the law 4.048 from January 22nd, 1942. The reform of elementary and middle schools with the law 5.692 from August 11th, 1971 and the professional and technical education. The creation of the Federal Network of Professional Education, Science and Technology that creates the Institutes of Education, Science and Technology with the law 11.892 from December 29th, 2008. We focused on looking deep into the origin and defenitions the term “skills” and the teaching trough skills in the industrial era in Brazil and other countries since the 90’s. To clarify the implementation and functionality we searched for experiences in SENAIs schools in the state of Santa Catarina and its usage in a school in the regional department of the state of Amazonas in Manaus. These experiences proved the effectiveness and quality of learning when the teaching of “learning doing it” is an expression of the same branch, theory and practice speak the same language in the mobilization of knowledge. We point out that to establish the Abilities Methodology by the teacher, students and schools its necessary its appropriation intrinsically and extrinsically given the conditions to knowledge and development of the scientific spirit of the proposal. It’s the schools commitment to involve itself in the search for knowledge providing above all to the teachers technical, scientific and pedagogical training. As a result of this research we developed and implemented a Learning Situation script of conflict management in classrooms for teachers training mediated by the Abilities Methodology.